A convenient route to a norbornadiene adduct of iridium with chelating phosphines, [Ir(R2PCH2CH2PR2)(NBD)][BAr4F] and a comparison of reactivity with H2 in solution and the solid-state - Chadwick, F; Olliff, N; Weller, A (Elsevier, 2015)
The straightforward synthesis of two cationic iridium norbornadiene species bearing simple bidentate phosphines is reported [Ir(R2PCH2CH2PR2)(NBD)][BAr4F] [NBD = norbornadiene; R = tBu, Cy; ArF = 3,5-C6H3(CF3)2]. The hydrogenation of [Ir(tBu2PCH2CH2PtBu2)(NBD)][BAr4F] in the solution phase and in the solid state is described in which saturated (solution) or unsaturated (solid-state) dimeric species with bridging hydrides are formed. The solid-state structures, as determined by single crystal X-ray diffraction, of these dimeric species are also discussed.